With Dilemma on Restriction Limits of the Medical Data Protection in the Republic of Serbia – Constitutional Aspect - Rajić, Nataša (Zbornik radova Pravnog fakulteta u Novom Sadu, 2019)
Right to personal data protection is guaranteed by the Constitution of the Republic of Serbia. This human right covers the protection of all kind of personal data, including information relating to patient`s medical condition. The paper deals with the issue of the permissible restrictions of this right, with particular reference to the protection of the health of others, as a permissible reason of restrictions. In a boarder sense, the paper deals with the relationship between two basic human rights: right to personal data protection and right to health protection (of others). The normative framework is consisted of Constitution of the Republic of Serbia, ratified international human rights treaties (especially the European Convention on the Protection of Human Rights and Fundamental Freedoms) as well as laws relating to the field of health care.